2005
DOI: 10.1590/s0103-84782005000200030
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da suplementação concentrada em pastagem de Tifton-85 sobre os componentes não carcaça de cordeiros

Abstract: Este estudo objetivou realizar uma análise dos componentes não carcaça ("quinto quarto") de cordeiros submetidos a diferentes níveis de suplementação concentrada em pastagem de Tifton-85. Utilizaram-se 25 cordeiros, machos castrados, sem raça definida, os quais receberam em condição de pastejo, diferentes níveis de suplementação: 0%, 1,0%, 1,5%, 2,0% ou 2,5% do peso vivo. O alimento concentrado utilizado foi fornecido pela empresa BÜNGE alimentos, ração Sano Vitosan, com o nome comercial de ovino criador. Após… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 4 publications
4
5
0
7
Order By: Relevance
“…Frescura et al (2005) found average values for head weight of 1.013 kg and 1.31 kg for blood of crossbred lambs in confinement. Carvalho et al (2005), working with crossbred animals and different levels of supplementation (% weight) on pasture and slaughtered at 28 kg, found weight of head of 1.116 kg and 1.194 kg for 0% and 2.5%, supplementation and weight of blood of 1.028 kg for 0% and 1.326 kg for 2.5% supplementation, similar to the values found in this work.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Frescura et al (2005) found average values for head weight of 1.013 kg and 1.31 kg for blood of crossbred lambs in confinement. Carvalho et al (2005), working with crossbred animals and different levels of supplementation (% weight) on pasture and slaughtered at 28 kg, found weight of head of 1.116 kg and 1.194 kg for 0% and 2.5%, supplementation and weight of blood of 1.028 kg for 0% and 1.326 kg for 2.5% supplementation, similar to the values found in this work.…”
Section: Resultssupporting
confidence: 87%
“…The degradation rate can be influenced by dry matter, as well as cellular and soluble carbohydrate content. Carvalho et al (2005), working with crossbred animals with different levels of supplementation (% weight) on pasture found that the proportions of full guts (9.17 kg for 0% and 6.925 kg for 2.5% supplementation), empty guts (2.609 kg to 2.537 kg for 0 to 2.5% supplementation) and gastrointestinal contents (6.561 kg to 4.352 kg for 0 to 2.5% supplementation) decreased slowly as the level of concentrate supplementation increased.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, non-carcass components represented nearly 50% compared with the EBW, which is consistent with Carvalho et al (2005), who affirmed that non-carcass components might account for more than 50% of the live weight of the animals, and this percentage is influenced by factors such as diet and other parameters responsible for the variation in the live weight of animals. Also, 28.43% of edible non-carcass components were obtained, which is very similar to the 26.94% obtained by Medeiros et al (2008), who assessed the effects of concentrate levels on non-carcass components of Morada Nova ovines in feedlot.…”
Section: Resultssupporting
confidence: 86%
“…Non-carcass body components are important parts that should be studied more carefully, especially because they infl uence the yield of the edible parts of the animal that are economically valuable and because some components are directly related to basal metabolism. According to CARVALHO et al (2005), the relative weight of non-carcass components ranges from 40 to 60% of live weight. This proportion is infl uenced by genetics, age, live weight, sex, type of birth and diet.…”
Section: Introductionmentioning
confidence: 99%